Dyrk1b promotes hepatic lipogenesis by bypassing canonical insulin signaling and directly activating mTORC2 in mice - Bhat, Neha; Narayanan, Anand; Fathzadeh, Mohsen; Kahn, Mario; Zhang, Dongyan; Goedeke, Leigh; Neogi, Arpita; Cardone, Rebecca L.; Kibbey, Richard G.; Fernandez-Hernando, Carlos; Ginsberg, Henry N.; Jain, Dhanpat; et al. (The Journal of clinical investigation, 2022)
Mutations in Dyrk1b are associated with metabolic syndrome and nonalcoholic fatty liver disease in humans. Our investigations showed that DYRK1B levels are increased in the liver of patients with nonalcoholic steatohepatitis (NASH) and in mice fed with a high-fat, high-sucrose diet. Increasing Dyrk1b levels in the mouse liver enhanced de novo lipogenesis (DNL), fatty acid uptake, and triacylglycerol secretion and caused NASH and hyperlipidemia. Conversely, knockdown of Dyrk1b was protective against high-calorie-induced hepatic steatosis and fibrosis and hyperlipidemia. Mechanistically, Dyrk1b increased DNL by activating mTORC2 in a kinase-independent fashion. Accordingly, the Dyrk1b-induced NASH was fully rescued when mTORC2 was genetically disrupted. The elevated DNL was associated with increased plasma membrane sn-1,2-diacylglyerol levels and increased PKCε-mediated IRKT1150 phosphorylation, which resulted in impaired activation of hepatic insulin signaling and reduced hepatic glycogen storage. These findings provide insights into the mechanisms that underlie Dyrk1b-induced hepatic lipogenesis and hepatic insulin resistance and identify Dyrk1b as a therapeutic target for NASH and insulin resistance in the liver.